REVERSAL OF HEMORRHAGIC-SHOCK IN RATS BY OXOTREMORINE - THE ROLE OF MUSCARINIC AND NICOTINIC RECEPTORS, AND AV3V REGION - (:unkn) unknown (ELSEVIER SCIENCE BV, 1994)
In an experimental model of hemorrhagic shock resulting in the death of almost all rats within 20-30 min, centrally active cholinomimetic drugs are reported to induce a prompt, sustained and dose-dependent improvement in blood pressure and survival rate claimed to be due to nicotinic, but not muscarinic actions. In the present study, cholinergic receptor agonist, oxotremorine (50 mu g/kg, i.v.) increased mean arterial pressure (from 22 +/- 1 to 123 +/- 3 mm Hg) and 60 min-survival rate (from 0 to 92%) in rats bled to hypovolemic shock. Atropine (2 mg/kg, i.v.) pretreatment inhibited the presser effect of oxotremorine significantly, but did not modify its effect on survival rate. On the other hand, pretreatment with mecamylamine (50 mu g, i.c.v.) almost abolished the reduction in mortality rate, but inhibited the presser effect of oxotremorine, partially. These results indicate that oxotremorine-induced presser response and decrease in mortality in rats with severe hemorrhagic shock are primarily mediated via central muscarinic and nicotinic receptors, respectively. AV3V region was previously reported to be involved in presser and natriuretic effects of i.c.v. carbachol in normotensive rats. In the present study, the electrolytic lesions of AV3V region significantly inhibited oxotremorine-induced increases in both blood pressure and survival rate in rats subjected to hemorrhagic shock. These findings indicate that AV3V region plays a major role in cholinergic cardiovascular control in hypotensive animals as well as normotensives.
Keywords: HEMORRHAGIC SHOCK; OXOTREMORINE; MUSCARINIC; ATROPINE; NICOTINIC; MECAMYLAMINE; AV3V LESION; VASOPRESSIN RELEASE; CHOLINERGIC MECHANISMS; HYPERTENSIVE RESPONSE; NATRIURETIC RESPONSES; CHOLINOMIMETIC DRUGS; BRAIN ACETYLCHOLINE; CENTRAL INJECTION; CONSCIOUS RATS; LESIONS; ACTH